2018
DOI: 10.3389/fneur.2018.00697
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation and Sleep-Wake Disturbances in Parkinson Disease: A Review

Abstract: Sleep-wake disturbances are common non-motor manifestations in Parkinson Disease (PD). Complex pathophysiological changes secondary to neurodegeneration in combination with motor symptoms and dopaminergic medications contribute to development of sleep-wake disturbances. The management of sleep complaints in PD is important as this symptom can affect daily activities and impair quality of life. Deep brain stimulation (DBS) is an effective adjunctive therapy for management of motor symptoms in PD. However, its e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 68 publications
(88 reference statements)
2
37
0
Order By: Relevance
“…This would serve a crucial unmet need in this patient population (Chaudhuri et al., ), as there are currently no effective treatments with a low side‐effect burden (Arnulf et al., ). Although DBS is an established therapy for the treatment of motor symptoms of Parkinson's disease, the effect of DBS on the sleep disturbances of Parkinson's disease has not yet been fully characterized, and the mechanism(s) underlying the improvements reported in sleep quality, efficiency and duration remains to be elucidated (Sharma, Sengupta, Chitnis, & Amara, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would serve a crucial unmet need in this patient population (Chaudhuri et al., ), as there are currently no effective treatments with a low side‐effect burden (Arnulf et al., ). Although DBS is an established therapy for the treatment of motor symptoms of Parkinson's disease, the effect of DBS on the sleep disturbances of Parkinson's disease has not yet been fully characterized, and the mechanism(s) underlying the improvements reported in sleep quality, efficiency and duration remains to be elucidated (Sharma, Sengupta, Chitnis, & Amara, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our prior work, we used a support vector machine (SVM) model that performed well when tested on novel epochs derived from the familiar patient used to train the model but failed to generalize to novel subjects (Thompson et al, 2018 (Arnulf et al, 2000). Although DBS is an established therapy for the treatment of motor symptoms of Parkinson's disease, the effect of DBS on the sleep disturbances of Parkinson's disease has not yet been fully characterized, and the mechanism(s) underlying the improvements reported in sleep quality, efficiency and duration remains to be elucidated (Sharma, Sengupta, Chitnis, & Amara, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of this study lie primarily in the seasonality of asthma attacks (48) and the diversity of routine medical treatment for patients with asthma (49). Thus, the inconsistent regular treatments of asthma may be a confounding of our results.…”
Section: The Quality Control Programmentioning
confidence: 89%
“…77,78 Specifically, significant improvements occurred in most PSQI subscores (ie, sleep quality, sleep latency, sleep efficiency, sleep duration) and PDSS sleep quality, sleep onset, and maintenance insomnia items. 77,78 In addition, improvements in objective PSG parameters have also been noted (wake after sleep onset time, sleep efficiency). Although insomnia is not a primary indication for DBS, improvements in sleep may be an added benefit.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…Most studies have examined subthalamic nucleus DBS and have shown improvements in PSQI or PDSS scores from pre‐ to postimplantation at variable periods (1 week–26 months) . Specifically, significant improvements occurred in most PSQI subscores (ie, sleep quality, sleep latency, sleep efficiency, sleep duration) and PDSS sleep quality, sleep onset, and maintenance insomnia items . In addition, improvements in objective PSG parameters have also been noted (wake after sleep onset time, sleep efficiency).…”
Section: Nonpharmacological Treatments Of Insomnia In Pdmentioning
confidence: 99%